Phylogenomic analysis reveals bees and wasps (Hymenoptera) at the base of the radiation of Holometabolous insects - Savard, Joël; Tautz, Diethard; Richards, Stephen; Weinstock, George M.; Gibbs, Richard A.; Werren, John H.; Tettelin, Hervé; Lercher, Martin J. (Genome Research, 2006)
Comparative studies require knowledge of the evolutionary relationships between taxa. However, neither morphological nor paleontological data have been able to unequivocally resolve the major groups of holometabolous insects so far. Here, we utilize emerging genome projects to assemble and analyze a data set of 185 nuclear genes, resulting in a fully resolved phylogeny of the major insect model species. Contrary to the most widely accepted phylogenetic hypothesis, bees and wasps (Hymenoptera) are basal to the other major holometabolous orders, beetles (Coleoptera), moths (Lepidoptera), and flies (Diptera). We validate our results by meticulous examination of potential confounding factors. Phylogenomic approaches are thus able to resolve long-standing questions about the phylogeny of insects.